Raman identification of the different glazing technologies of Blue-and-White Ming porcelains. Issue 2 (15th January 2022) - Colomban, Philippe; Ngo, Anh-Tu; Edwards, Howell G.M.; Prinsloo, Linda C.; Esterhuizen, L. Valérie
Abstract: Shards of Blue-and-White Ming porcelain from shipwrecks of Portuguese ships found on the coasts of South Africa plus a shard from Mombasa (Kenya) were analyzed by optical microscopy, SEM-EDS and Raman microspectroscopy (458 nm). Whereas the Raman signature of porcelain body paste compositions which are based on mullite, quartz and an amorphous phase with the minor presence of anatase and feldspar are very comparable whatever the variable alumina content, at least two types of glazes are observed: a high-temperature soda-potassium glaze, and glazes richer in calcium and similar to a celadon glaze (with the possibility of wollastonite formation). The blue decoration is obtained with a material rich in manganese typical of the Ming productions. Some shards exhibit a two-layer glaze and the blue decoration is either placed under-glaze, or in-glaze as found in the Vietnamese productions of the same period. Previous assignments of the Raman signature of feldspar to cobalt aluminate are now not favoured (blue colour is obtained with Co 2+ ions dissolved in the glassy silicate) and several black spots exhibit the characteristic spectrum of an epsilon Fe2 O3 phase being present. Graphical abstract: Image 1 Highlights: Raman and SEM-EDS evidence of Ca-rich and Ca-poor glaze of Blue-and-White Ming porcelain from shipwrecks of Portuguese ships. The blue decoration is either placed under-glaze, or in-glaze as found in the Vietnamese productions of the same period. Previous assignments of the Raman signature of feldspar to cobalt aluminate are now not favoured.